Minuman Pongasi dalam Ritual Adat Tolaki - Arliana, Riska; Alkausar, Muh; Almarsaban, Almarsaban (JURNAL KABANTI: Kerabat Antropologi, 2024)
The pongasi drink in Tolaki traditional rituals is a legacy from our ancestors that has become a habit in society. This research aims to understand the existence of pongasi drinks in Tolaki conventional rituals in the past and present. This research reads data using two theories: functional structural theory according to Radcilffe-Brown (1979) and universal social evolutionary theory according to Herbert Spencer (1820). Data collection techniques in this research are involved observation, in-depth interviews and documentation. The results of this research show that pongasi drinks are drinks that must be served and cannot be separated from Tolaki traditional rituals. As time goes by, there are social changes in its existence, namely, apart from traditional Tolaki rituals, nowadays pongasi drinks have also been used as a medicine for tiredness, as a source of income, and as a link between communities. This can happen due to environmental factors in society which has now become a complex society. Thus, given these conditions, it can be understood that the pongasi drink in Tolaki traditional rituals can survive and change depending on the social structure in a society